Analysis of Antibiotics in Bivalves by Ultra-High Performance Liquid Chromatography-Quadrupole Time-of-Flight Mass Spectrometry - André M. P. T. Pereira; Andreia Freitas; Angelina Pena; Liliana J. G. Silva (MDPI AG, 2023)
The presence of pharmaceuticals in aquatic ecosystems mostly originates from wastewater treatment plants (WWTPs) and such a situation can be responsible for significant negative impacts on natural ecosystems, such as estuarine and coastal areas. Bioaccumulation of pharmaceuticals, namely antibiotics, in exposed organisms is known to have remarkable effects on different trophic levels of non-target organisms such as algae, invertebrates and vertebrates, including the emergence of bacterial resistance. Bivalves are a highly appreciated seafood product, as they are fed by filtering water, and can bioconcentrate chemicals, being ideal for biomonitoring environmental health hazards in coastal and estuarine ecosystems. To use this sentinel species, an analytical strategy was developed to be used in accessing antibiotics, from human and veterinary medicine, and evaluate their occurrence as emerging pollutants in aquatic environments. The optimized analytical method was fully validated according to the European requirements defined by the Commission Implementing Regulation 2021/808. The validation comprised the following parameters: specificity, selectivity, precision, recovery, ruggedness, linearity, and the decision limit CCα, as well as the limit of detection (LoD) and limit of quantification (LoQ). The method was validated for 43 antibiotics to allow their quantification in both contexts, environmental biomonitoring and food safety.